Governança corporativa: geração de valor - um estudo das empresas brasileiras de capital aberto com ações negociadas na bolsa de valores de São Paulo no período 2000 até 2011 - Birk, Gabriela (2012)
Since the early 1980s the Corporate Governance has become the main global focus of discussion about the top management. In Brazil the topic has gained impact from 1995, the foundation year of the IBCA (Instituto Brasileiro de Conselheiros de Admininstração), current IBGC (Instituto Brasileiro de Governança Corporativa). The adoption and improvement of corporate governance practices are fundamental to the development of capital markets, which is essential for growth and competitiveness of Brazilian companies. The corporate governance practices to achieve greater transparency of companies in relation to the market, commit themselves to rules and procedures that are not imposed on other companies listed on BOVESPA. Thus, the main objective of this dissertation is to analyze the economic effects associated with adherence to the Levels of Corporate Governance. In this context, it is assumed that companies who adopt these practices have a different valuation of their shares substantially higher compared those who do not comply. For this, we analyzed the daily stock returns of companies listed on BM&FBOVESPA who adopted to NDGC in the period 2000 to 2011. Some companies that were already listed on the Bolsa de Valores changed segment, other now joined NDGC on the ticket (IPO). This work breaks new ground in three fronts: coverage and analysis period had hitherto been made only sectorial analysis and less time and the methodology used (models ARCH/GARCH, specific financial series). The results demonstrate, from the methodological option, there would be no generation of value for companies with adoption of corporate governance, so the negative response to the central question of this work. However, the governance index return presents differently in relation to the BOVESPA index, suggesting that firms with IPO and automatic membership to the level of corporate governance in the period were decisive to explain the different performance of this market segment.